Structure and tree diversity of an inland Atlantic Forest–A case study of Ponte Branca Forest Remnant, Brazil - Antonio Tommaselli; Nilton Imai; Adilson Berveglieri; Mariana Thomaz; Gabriela Miyoshi; Baltazar Casagrande; Raul Guimarães; Eduardo Ribeiro; Eija Honkavaara; Mariana Campos; Raquel de Oliveira; Hassan David; Rorai Martins-Neto (Faculty of Geography, Universitas Gadjah Mada, 2022)
The Atlantic Forest is the most fragmented and threatened domain in Brazil. The main remnants are in the coastal regions. This paper describes a study performed at a protected federal reserve in Brazil located in western of São Paulo state, which is a transition with the Savannah. A forestry survey was made for understanding the forest structure, diversity, and floristic composition of an inland Atlantic Forest area. A total of 3,181 individuals with a Diameter at Breast Height over 3.5 cm were sampled. The data sample was composed of 29 families and 64 species from 15 plots. Forty-seven percent of the species were classified as a pioneer, 42% as secondary, and 11% as climax. The species Eugenia uniflora presented the highest importance value index. The values of Shannon-Weaver diversity and Pielou equitability index indicate the area has less diversity than others in the same phytophysiognomy and was dominated by a few species with many individuals. Several anthropogenic disturbances altered the forest cover of the Ponte Branca Forest remnant, which is in the process of secondary succession.